Pt nanoparticles/MoS2 nanosheets/carbon fibers as efficient catalyst for the hydrogen evolution reaction. (1st June 2015) - Hou, Dongman; Zhou, Weijia; Liu, Xiaojun; Zhou, Kai; Xie, Jian; Li, Guoqiang; Chen, Shaowei
Abstract: Advanced materials for electrocatalytic water splitting are central to renewable energy research. In this study, we describe a two-step reaction for preparing hydrogen evolution reaction (HER) electrodes composed of Pt nanoparticles and MoS2 nanosheets grown on carbon fibers. The morphology and the structures are characterized by a variety of techniques including SEM, TEM, XRD and XPS. Detailed electrochemical characterizations demonstrate that the Pt nanoparticles/MoS2 nanosheets/carbon fibers electrode (2.03 w% Pt) exhibited an excellent catalytic activity for HER in an acidic electrolyte with an overpotential of −5 mV (vs. HER). And the corresponding Tafel slope is estimated to be 53.6 mV/dec. Stability tests through long-term potential cycles and extended electrolysis confirm the exceptional durability of the catalyst.